Hubungan Asupan Makan, Status Gizi, Dan Usia Menarche Ibu Dengan Menarche Dini Pada Remaja Putri Di Wilayah Perumahan Bumi Pertiwi 2, Kabupaten Bogor: The Relationship Of Dietary Intake, Nutritional Status, And Maternal Age Of Menarche With Early Menarche In Adolescents In The Perumahan Bumi Pertiwi 2, Bogor - Widya Siestianing Rachma; Ikha Deviyanti Puspita (Poltekkes Kemenkes Palu, 2021)
There has been a decrease in the age of menarche in the last few years. Various degenerative diseases can appear due to early menarche, women with early menarche have a relatively higher risk of heart disease, breast cancer, and increase 2.3 times the risk of metabolic syndrome regardless of ethnicity and race. Early menarche can be caused by genetic factors or changes in environmental factors, maternal age of menarche (genetic), nutritional status,and lifestyle. The purpose of this research is to find out the relationship of dietary intake, nutritional status, and maternal age of menarche with early menarche in adolescents in the Perumahan Bumi Pertiwi 2, Bogor. This study uses a cross sectional design with research subjects is adolescents with aged 10-14 years and life in the Perumahan Bumi Pertiwi 2 as many as 40 people. The variables studied in this study were food intake, nutritional status, and age of maternal menarche. The results of this study are there is a relationship between protein intake and nutritional status with the age of menarche, while the energy intake, fat, carbohydrates, calcium, and the age of maternal menarche have no relationship with the age of menarche in adolescents in the Bumi Pertiwi 2